Efektivitas layanan konseling kelompok untuk mengurangi kecemasan berbicara di depan umum pada siswa SMK Islam Wijaya Kusuma - Nelawati Airunnisah; Devi Ratnasari; Mulyadi Mulyadi (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2019)
The purpose of this reseach is to find out about “Effectiveness of Group Counseling Services to Reduce Anxiety in Public Speaking at Wijaya Kusuma Islamic Vocational School Jakarta”. The research method used in this study is a quantitative research : if with the Pre-experimental research method using one group pretest postest design. Data and sources of data in this study were students of class X AK-2 and X AP-1 Wijaya Kusuma Islamic Vocational School Jakarta, the total population of 64 students and reseach subjects or samples as many as 10 students with sampling using purposive sampling technique. The instrument used was an anxiety questionnaire in public speaking. Data analysis techniques were carried out by means of non-parametric statistical test using the Wilcoxon Signed Rank test. The results of the study concluded that in general group counseling services were effective to reduce anxiety in public speaking. It can be seen clearly that the probability value of Asmyp. Sig (2-Tailed) speaking anxiety of students in the reserch subjects amounted to 0,005 or probability values below alpha 0,05 (0,005 < 0,05). The results of this study are useful for schools in designing guidance and counseling programs to be more effective in helping develop potential and alleviate student problems